History Matters: Chinese Urbanisation as an Emergent Space. (May 2018) - Sun, Yimin; Lisaia, Daria
This article explores the process of urbanisation in China in the context of three historical transformations spanning the period 1840–2017. During the first two transformations urbanisation took place slowly, with the fragmented development of cities without a systemic character. This laid the foundation for the third historical transformation, the policy of reforms and openness in 1978, which opened up opportunities for the development of cities and stimulated a wave of internal labour migration. Over the last 30 years, urbanisation in China has acquired a huge scale, becoming a powerful tool for the development of the country's economy. Initially a spontaneous development, in the 2000s urbanisation began to acquire a strategically planned approach. In 2014, the Central Committee of the Communist Party of China (CPC Central Committee) announced the adoption of a 'National New-Type Urbanisation Plan' (2014–2020), which marked a qualitative transition in terms of the management of the urbanisation process. This article argues that a nuanced historical analysis of China's urbanisation is key to studying its urban future.